PENGARUH INTELLECTUAL CAPITAL DAN INTELLECTUAL CAPITAL DISCLOSURE TERHADAP KINERJA KEUANGAN PERUSAHAAN - Faradina, Ike; Gayatri, . (E-Jurnal Akuntansi; Vol 15 No 2 (2016), 2016)
This study aims to determine the effect of Intellectual Capital and Intellectual Capital Disclosure Financial Performance Against Companies incorporated in LQ45 Index 2010-2014. The results of the study could provide insight for stakeholders to understand the Intellectual Capital and Intellectual Capital Disclosure in the business activities of the company in order to provide value added and can meniciptakan competitive advantage for the company. Total sample of 8 companies acquired by purposive sampling technique. Data analysis techniques in this study using multiple linear regression and data collection is done by non-participant observation in the form of documentation. The analysis showed that the Intellectual Capital (IC) and the Intellectual Capital Disclosure positive effect on return on assets (ROA).
Keywords: Intellectual Capital, Intellectual Capital Disclosure, Return On Asset